2020
DOI: 10.1111/bjh.16436
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies in the treatment of AL amyloidosis: co‐targetting the plasma cell clone and amyloid deposits

Abstract: Immunoglobulin light-chain amyloidosis (AL amyloidosis) is a rare disease in which a small plasma cell clone produces toxic misfolded proteins that deposit in organs and impair their function. Currently, the only available treatment approach is the elimination of clonal plasma cells. However, a rapid strike that halts and possibly reverses organ damage is crucial. The development of agents that facilitate the clearance of pathological fibrillar deposits, therefore reducing the frailty of patients, is the neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…18 patients chose this regimen in our study, with the 1-year survival rate was 70.6% which was lower than that in foreign studies. Recent studies have shown that monoclonal antibodies can not only provide treatment against malignant plasma cells, but also target and remove amyloid from organs, with the advantages of high selectivity and low toxicity, becoming one of the expected clinical treatments in the future (37,38).AA amyloidosis is mainly associated with long-term in ammatory conditions (39,40), and treatment is based on the control of in ammation, clinically mainly using factors, antibiotics, colchicine and other treatments (41,42). For patients with poor e cacy or severe organ failure, organ transplantation was performed.…”
Section: Discussionmentioning
confidence: 99%
“…18 patients chose this regimen in our study, with the 1-year survival rate was 70.6% which was lower than that in foreign studies. Recent studies have shown that monoclonal antibodies can not only provide treatment against malignant plasma cells, but also target and remove amyloid from organs, with the advantages of high selectivity and low toxicity, becoming one of the expected clinical treatments in the future (37,38).AA amyloidosis is mainly associated with long-term in ammatory conditions (39,40), and treatment is based on the control of in ammation, clinically mainly using factors, antibiotics, colchicine and other treatments (41,42). For patients with poor e cacy or severe organ failure, organ transplantation was performed.…”
Section: Discussionmentioning
confidence: 99%
“…137 In addition, monoclonal antibody technology is a recent therapeutic approach in the treatment of cardiac amyloidosis with a favourable safety profile, well-tolerability and highly clinical effectiveness. 138 One mechanism of monoclonal antibodies is to directly target either the amyloid intermediates or fibrils, thereby removing existing amyloid deposits. 139 In AL cardiac amyloidosis, anti-misfolded light chains antibody birtamimab (NEOD001), 140 CAEL-101 141 and antiserum amyloid P-component antibody dezamizumab have been tested in clinical studies and found to diminish amyloid burden in various organs in patients, without any significant toxicity.…”
Section: Other Novel Anti-misfolding Protein Strategiesmentioning
confidence: 99%
“…A number of immunomodulatory agents (pomalidomide, thalidomide), small interfering RNA (patisiran), antisense oligonucleotides (inotersen), TTR tetramer stabilizers (tafamidis, tolcapone, AG10) are actively being tested in clinical trials and show beneficial effects 137 . In addition, monoclonal antibody technology is a recent therapeutic approach in the treatment of cardiac amyloidosis with a favourable safety profile, well‐tolerability and highly clinical effectiveness 138 . One mechanism of monoclonal antibodies is to directly target either the amyloid intermediates or fibrils, thereby removing existing amyloid deposits 139 .…”
Section: Anti‐misfolding Protein Strategies In Cardiovascular Diseasesmentioning
confidence: 99%
“…Preparation of IL-35 monoclonal antibody in the treatment of liver diseases may promote liver healing and reduce side effects. On the other hand, CRISPR-Cas9 genome editing system provides a tremendous promising strategy for versatile and high specifically targeting genome editing (Popkova et al, 2020). Genome editing also involves the precise manipulation of cellular DNA sequences to alter cell fates and organism traits, that has been widely applied in treating various genetic diseases (Deng et al, 2020).…”
Section: Future Expectationmentioning
confidence: 99%